Can education and training improve the adoption of a psychosocial group treatment by dementia services?. (October 2019) - Cheung, Gary; Peri, Kathy
Objective: Cognitive stimulation therapy (CST) is a psychosocial group treatment for people with dementia. The aims of this project were to (a) evaluate the effectiveness of a one-day training workshop; (b) measure the uptake of CST following the workshops; and (c) explore the barriers of implementing CST. Method: Ten workshops were conducted. Attendees completed a self-evaluation at the end of the training day and were later invited to complete an online survey enquiring about implementation. Results: Two hundred and fourteen workshop attendees completed the self-evaluation. The mean self-rated knowledge and skills for conducting and facilitating CST (1 = No skills, 5 = Very good skills) was 2.3 (SD = 1.2) and 4.3 (SD = 0.7) before and after the workshop, respectively ( p = 0.000). The mean self-rated confidence for applying learning to conducting and facilitating CST was 4.2 (SD = 0.7) (1 = Not confident, 5 = Very confident). There were 11 CST programmes started after the workshops and another 10 sites were in the process of starting CST programmes. The main barriers of implementation were lack of staff time/funding and problems of finding suitable participants with dementia. Conclusions: The one-day training workshop is an effective method to disseminate CST. Addressing the barriers identified could improve the adoption of CST in practice.